AN EVALUATION OF THE PERFORMANCE OF SECRETARIAL STUDENTS ON INDUSTRIAL WORK EXPERIENCE SCHEME: A CASE STUDY OF NIGERIAN UNIVESITIES - S., Amoor S. (Sokoto Educational Review, 2018)
Students industrial work experience scheme (SIWES) programme is purposefully designed to bridge the gap between the theory and practice for students from tertiary institutions. This paper examines the success of SIWES in the provision of practical skills and competence to secretarial students from Nigerian universities in office technology and information systems. A research question and null hypothesis were formulated and data collected from 215 final year students of 2008/2009 session and 32 lecturers of business education section from five selected Nigerian universities. A six-item questionnaire was generated for data collection. Percentage and frequencies were used to analyse the research question, while T-test was used to test the null hypothesis at the significant level 0.05. the findings revealed that university secretarial graduating students did not acquire the desired knowledge, skill and competences in modem office technology and information systems while on SIWES. Many of them did not get appropriate placement where they could benefit from these practical skills and competence. The paper recommends that the departmental model offices should be adequately equipped with modem office equipment such as computer, scanner, digital fax machine, digital copier, mobile note-taker, to adequately expose secretarial students to modem office technology and information systems while still in the school.